Taxonomic revision of the subterranean genus Virpazaria Gittenberger, 1969 (Gastropoda, Spelaeodiscidae) - Fehér, Zoltán; Deli, Tamás; Erőss, Zoltán P.; Lika, Romilda (European Journal of Taxonomy, 2019)
Virpazaria Gittenberger, 1969 is distributed in the Balkan Peninsula (Albania, Montenegro and Croatia) and inhabits the shallow subterranean habitat (MSS) on limestone base rock. Reviewing historical and recently collected material, two species, Virpazaria (Virpazaria) gittenbergeri Fehér & Erőss sp. nov. and Virpazaria (Virpazaria) pesici Fehér & Deli sp. nov., are introduced as new to science. The conservation status of the new species are assessed using IUCN criteria. Two taxa, Virpazaria (Virpazaria) pageti alexanderi Reischütz & Subai, 2012 and Virpazaria (Aemiliella) ripkeni pastorpueri Reischütz et al., 2011, are synonymized with their nominate subspecies. Some new distribution records, as well as geological and geomorphological data about the known locations for Virpazaria, are presented.